Toward More Adequate Selection Criteria: A Case Study of Graduate Counselling Admissions - Pass, Larry E.; Scherer, Shawn E. (Canadian Journal of Counselling and Psychotherapy, 2012)
An initial attempt was made to consider the process employed in selecting applicants for doctoral training in counselling through systematically investigating the admission criteria used by the faculty of one counselling department. While a number of the categories considered were commonly acknowledged as having considerable weight in the decision to accept or reject an applicant, of the total number available approximately 45% were regarded as unimportant in making an assessment. There was also substantial diversity of opinion among faculty as to the significance given to a number of other categories. To the extent that the counselling faculty investigated are representative of others, the findings may have general applicability to many counselling departments.